Applying principles of historical critique: authentic oral history? - Oelofse, Marietjie (Faculty of Humanities, University of the Free State, 2011)
To reconstruct the past, oral historians are concerned with the depths of memory as a potential source of information, evidence and meaning at their disposal. Unfortunately, memory can never be absolutely certain, wherein lies its weakness as a source of knowledge of the past. The researcher has the important task of implementing historical interpretation and principles of historical critique in searching for authenticity in sources. Taking into account the nature of memory and the factors that may negatively affect its objectivity, the article will examine which reliable techniques and methods may be implemented by the oral historian to minimise problems and inaccuracies, as well as examine oral evidence for factual credibility.
Keywords: Reconstruct the past; Knowledge of the past; Historical interpretation; Oral historians; Authenticity in sources; Factual credibility